Oesophageal Carcinoma : Trends and risk factors in rural Bangladesh - Shil, BC; Islam, MA; Nath, NC; Ahmed, F (Journal of Dhaka Medical College, 2010)
On a worldwide basis, cancer of esophagus is the sixth most common malignancy. In developing countries it ranks third in frequency and has one of the worst prognoses of any neoplasm of the human body. It is essential to detect the malignancy early and to determine the extent of the disease to ensure the best option for a cure. The aim of this study was to evaluate the frequency and pattern of Oesophageal carcinoma with respect to age and sex groups and to determine the trends of histology, site distribution and risk factors of Oesophageal carcinoma. A prospective study was carried out in 102 patents with Oesophageal carcinoma between May 2007 and April 2010 in Laxmipur, Feni & Kushtia district. The data were recorded in prestructured proforma and analyzed later on. The site of tumor was classified as upper, mid & lower esophagus. A high frequency of cancer was seen in males with a total of 79 (77.5%) cases as compared to 23 (22.5%) females with male to female ratio of 3.43:1. Maximum number of the patients of Oesophageal carcinoma was seen in 5th and 6th decades of life. Dysphagia was the main presenting complain in 94.11 % of patients. Tobacco & betel nut chewing are strong risk factors for Oesophageal cancer. Squamous cell carcinoma was the most common malignancy seen in (97) 95.1% of patients. The remaining (5) 4.9% had Adenocarcinoma. Most of the Oesophageal carcinoma 49 (48.04%) were located in the lower third of esophagus followed by middle third 41 (40.19%). Key words: Oesophageal carcinoma; Risk factors; Trends of disease. DOI: 10.3329/jdmc.v19i1.6248 J Dhaka Med. Coll. 2010; 19(1) : 29-32.